Beautiful enemies : friendship and postwar American poetry - Epstein, Andrew, 1969- (Oxford University Press, 2006)
Focusing on the work and interrelations of some of the most important and influential postmodernist American poets, this text offers an interpretation of the peculiar dynamics of American avant-garde poetic communities, as it tells the story of a vibrant intellectual community where friendship and writing intersect in fascinating ways.